PENINGKATAN KEMAMPUAN MENULIS TEKS BERITA DENGAN METODE INVESTIGASI KELOMPOK PADA SISWA SMP - Listiyana Dwi; Iwan Somantri (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The background of this research is based on the events that occur in the field as evidenced by the acquisition of learning to write news texts on junior high school students in SMP MUTIARA 4 Bandung still unable to achieve the achievement standard of learning in writing news texts. This is because the teacher has not used the right learning method in writing news texts. The research problem formulation is about how planning, implementation, and learning outcomes to improve the ability to write news texts by using group investigation methods on students of SMP MUTIARA 4 Bandung. The implementation of this research was held in two cycles, namely, cycle I and II. The method used in this study is a qualitative method. The data of this study are the results of writing student news texts. Research data in the form of observations and evaluation results of students are processed qualitatively. The results showed that the group investigation method proved an increase in the results of the learning process of writing news texts of students at SMP MUTIARA 4 Bandung.